Polylactic acid (PLA) biocomposites filled with waste leather buff (WLB) - Ambone, Tushar; Joseph, Seena; Deenadayalan, E.; Mishra, Satyendra; Jaisankar, S.; Saravanan, P. (Journal of Polymers and the Environment, 2017)
A large amount of leather waste is generated from tanning industries and most of which are disposed of landfill or discharged into the natural water bodies without any treatment, causing environmental problems. The aim of this study is to develop eco-biocomposites using waste leather buff (WLB) as filler in Polylactic acid (PLA) matrix to reduce the environmental issues and provide sustainable solution. WLB/PLA composites were prepared by twins-screw micro extruder varying the WLB content from 2% to 30 wt%. These composite were extensively characterise by several techniques. Tensile properties of the composites showed addition of WLB resulted in improvement of tensile property of composite and reduction in percentage crystallinity of PLA matrix observed with increase in WLB content. The effect of WLB on properties of interfacial adhesion and dispersion in WLB/PLA composites were studied by SEM. Wettability of composites was tested by contact angle and water absorption studies. WLB/PLA composite showed increase in water absorption with WLB loading. These WLB/PLA composite could be used to develop low cost eco-friendly product material.

Processing and characterization of waste leather based polycaprolactone biocomposites - Joseph, Seena; Ambone, Tushar S.; Salvekar, Abhijit V.; Jaisankar, S. N.; Saravanan, P.; Deenadayalan, E. (Polymer Composites, 2017)
Waste leather buff (WLB) filled polycaprolactone (PCL) composites were prepared by twin-screw extrusion varying the WLB content from 2% to 40%. These composites were extensively characterized by several techniques in order to establish micro and macroscopic properties. Addition of WLB resulted in improvement of tensile modulus of neat PCL and reduction in percentage crystallinity of PCL matrix was observed with increase in WLB content. Interfacial adhesion and dispersion of WLB on PCL matrix was investigated using Scanning Electron Microscope. Percentage of water uptake increased with increase in concentration of WLB in the composite. These biodegradable composites could be used to develop low cost materials suitable for applications in footwear industry, for making bags, suitcases, etc., eliminating the environmental issues arising from WLB generated from tanneries in leather industry. POLYM. COMPOS., 38:2889-2897, 2017. (c) 2015 Society of Plastics Engineers